Observations on the Development of Mural Thrombi in Chronic Experimental Aneurysms in Sheep - Stehbens, W E (Thrombosis and Haemostasis, 1997)
Observations were made on mural thrombi in experimental venous pouch aneurysms in sheep. Thrombi associated with mural tears and dissection consisted predominantly of laminated fibrin masking the earlier platelet deposition and infiltrating the wall to some extent. Thrombus growth was associated with platelet masses of Zahn and secondary fibrin deposition. Intervening spaces contained a variable quantity of coagulated plasma, fibrin mesh, leucocytes, disintegrating red cells and platelets rather than red thrombus as often suggested. Periodic deposition of platelet masses with surface rippling, the whorling patterns of laminated fibrin and mechanical disruption of red cells indicated the importance of haemodynamics. Coarse macroscopic lamination of mural thrombi was attributed in part to recurrent dissections between the wall and the mural thrombus and of the thrombus itself. These accounted for growth of thrombus with expansion of the wall and interference with organization of the thrombus. The model has proved suitable for the study of thrombogenesis and thrombus behaviour in aneurysms.